Migration and gender in the mexican context: scientific literature review - Teresa Rebolledo Gámez; Mª Rocío Rodríguez Casado (FahrenHouse, 2014)
Female migration is a phenomenon with socioeducational considerations thar determine their analysis.The prensent article presents a literature review aims to analyze the aspect thar are discussed in relation to the issue of migration and gender in Mexico. Therefore, it has selected more than forty articles from magazines, discussion forums and books in the last decade hace collected reflexions and research on this reality. As a result of this review, it has taken three areas in the contributions published: Human Rights and policy migratory; female migration characteristics; and vulnerability and risk situation. Despite the thematic diversity, appear repeatedly ideas like the idiosyncasies of female migration, vulnerability and risk assumed by women in border transit and the violation of rights of women to political and institutional level. Received: 04/12/2013 / Accepted: 17/01/2014 How to reference this article Rebolledo Gámez, T., Rodríguez Casado, M. R. (2014). Migraciones y género en el contexto mexicano: revisión de la literatura científica. Foro de Educación, 12(17), pp. 165-185. doi: http://dx.doi.org/10.14516/fde.2014.012.017.008